2008
DOI: 10.1007/s10038-008-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype analyses in 136 patients with single large-scale mitochondrial DNA deletions

Abstract: We examined 136 patients with mitochondrial DNA (mtDNA) deletion. Clinical diagnoses included chronic progressive external ophthalmoplegia (94 patients); Kearns-Sayre syndrome (KSS; 33 patients); Pearson's marrow-pancreas syndrome (six patients); and Leigh syndrome, Reye-like syndrome, and mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (one patient). The length and location of deletion were highly variable. Only one patient had deletion within the so-called shorter arc betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 40 publications
(45 reference statements)
7
74
3
Order By: Relevance
“…Amongst these, mtDNA deletions are often associated with chronic progressive ophthalmoplegia (OMIM 157640, 609286, 258450, 610131, 609283, 258400), Kearns-Sayre syndrome (OMIM 530000), and Pearson marrow-pancreas syndrome (OMIM 557000; Yamashita et al 2008;Mancuso et al 2007). These deletions often occur in an area of the mitochondrial genome that encodes the two mitochondrial genes for ATP synthase, ATPase6 and ATPase8 (Mita et al 1990;Samuels et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these, mtDNA deletions are often associated with chronic progressive ophthalmoplegia (OMIM 157640, 609286, 258450, 610131, 609283, 258400), Kearns-Sayre syndrome (OMIM 530000), and Pearson marrow-pancreas syndrome (OMIM 557000; Yamashita et al 2008;Mancuso et al 2007). These deletions often occur in an area of the mitochondrial genome that encodes the two mitochondrial genes for ATP synthase, ATPase6 and ATPase8 (Mita et al 1990;Samuels et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the different mtDNA deletion sizes and phenotypic heterogeneity linked with these mutations have led to conflicting results. Larger mtDNA deletions have been associated with more severe disease and earlier disease onset 15, 16, 17, 18, 19. Whereas a highly significant,20 significant,15, 16, 21, 22 weak,18, 23 or no24 correlation has been reported between the percentage of COX‐deficient fibers and the degree of mtDNA heteroplasmy, most studies found no correlation between the biochemical defects and the nature of the deletion (the number of protein‐encoding genes and the complexes affected by the deletion) or deletion size alone 4, 15, 20, 22, 25.…”
mentioning
confidence: 99%
“…Therefore, fibers exhibiting high levels of deficiency involving other respiratory chain complexes might be missed. Despite few exceptions,16, 17, 19, 26 patients were also often evaluated as one group, without discriminating deletions of different sizes and locations. Such an analysis cannot determine whether the nature of the deletion influences biochemical and clinical profiles.…”
mentioning
confidence: 99%
“…Using this methodological approach, we were able to describe a novel large mitochondrial DNA deletion involving almost all genes on the big arc, flanked by short direct repeats, as often described for mtDNA deletions (Kleinle et al 1997;Yamashita et al 2008). We demonstrated this large deletion of mitochondrial DNA in at least three different tissues of this patient.…”
Section: Discussionmentioning
confidence: 54%
“…The patient reported by Boles et al (1998), who also presented with Addison disease, had a smaller deletion. On the other hand, there are cases with similar deletion sizes but without Addison disease, reinforcing the concept that genotype does not always or exactly correlate with phenotype (Yamashita et al 2008). Due to the genetic and clinical heterogeneity of mitochondrial disorders, it is especially important to have access to molecular analysis to confirm diagnoses and to achieve more precise genetic counseling (Wong 2007).…”
Section: Discussionmentioning
confidence: 78%